Dampak Abrasi Pulau Tiban, Desa Kartikajaya Kecamatan Patebon Kabupaten Kendal - Distira Andy Liawan; Mahmud Abdul Haris (Jurnal Teknik Sipil, 2021)
In mid-2017 there was a fairly large storm on the north coast of Java which resulted in quite a large amount of coastal abrasion in the tourist attraction "Pulau Tiban" Kartikajaya Village, Patebon District, Kendal Regency, so that tourism activities stopped. This research aims to determine the process of abrasion and the impact felt by the surrounding community due to the destruction of the tourist attraction "Pulau Tiban" in Kartikajaya Village. While the method used is observation with remote sensing methods, namely using the Google Earth application to determine the level of abrasion process from year to year and interviews to determine the impact of abrasion on tourist attraction activities. From the observations, it can be seen that sedimentation and accretion occurred from 2013 to 2017, experiencing a significant increase, reaching a maximum area of more than 8.2 hectares with an annual average of 1.27 hectares. Meanwhile, the abrasion that occurred in the 2017 to 2019 period and almost submerged the “Pulau Tiban” Beach Tourism Object of 2.5 ha/year. With the SPSS 26.0 application in 2020, the level of validity can be seen by comparing r count with Sig 1-tailed, data validity is seen if r count ? Sig.1-tailed with a significance of 0.05 or 5%. To find r table, where df=N-2 then r table is 0.3172 while the value of the sample question gets the value of r count=0.778 which is greater than the value of r table = 0.3172 so that the question is said to be valid.